Prolapsing Left Atrial Mass Presenting as Syncope - Pathare, Presheet; Weyand, Michael; Heim, Christian (The Thoracic and Cardiovascular Surgeon Reports, 2022)
Background Myxomas are the most common primary cardiac tumor in adults and are most commonly found within the left atrium. These are usually asymptomatic, detected incidentally, or present gradually with symptoms typical of heart failure.Case Description This case report is a description of a case of syncope caused by a large left atrial myxoma.Conclusion Atrial myxomas may present with transient loss of consciousness, especially when they prolapse through the atrioventricular valves or when embolization occurs. Non-invasive diagnostic tools (e.g., echocardiogram, cardiac computed tomography) should be considered to thoroughly evaluate cardiogenic causes of syncope.
Keywords: myxoma; neurological symptom; tumor, cardiac imaging